2011
DOI: 10.1159/000330189
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Steroids and Angiotensin Receptor Blockers for Patients with Advanced IgA Nephropathy and Impaired Renal Function

Abstract: Background/Aims: The therapeutic strategy for advanced IgA nephropathy patients with impaired renal function is still controversial. Patients and Methods: We divided 44 IgA nephropathy patients with an estimated glomerular filtration rate (eGFR) of less than 60 ml/min/1.76 m2 and proteinuria greater than 0.5 g/g · creatinine into two groups: the angiotensin receptor blocker (ARB) group (n = 22), treated with ARBs, and the steroid group (n = 22), treated with corticosteroid. We analyzed the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…For example, the number of advanced cases involving T2 and T3 in the Oxford analysis tended to be higher in the DILAZEP group, and the ACEI/ARB ratio was also higher in the DI-LAZEP group. In our previous reports, we demonstrated the long-term beneficial effects of RASIs on the prevention of end-stage renal disease; however, we could not show any effects causing significant decreases in the levels of U-Prot in the advanced IgAN cases (20,21), and the decreases in the levels of U-Prot caused by ARBs were greater than those caused by ACEIs in these cases (19). In addition, we could not deny that these differences between the groups accounted for the lack of significant decreases in the levels of U-Prot in the DILAZEP group, although the ability of RASIs to decrease the levels of U-Prot is widely recognized.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…For example, the number of advanced cases involving T2 and T3 in the Oxford analysis tended to be higher in the DILAZEP group, and the ACEI/ARB ratio was also higher in the DI-LAZEP group. In our previous reports, we demonstrated the long-term beneficial effects of RASIs on the prevention of end-stage renal disease; however, we could not show any effects causing significant decreases in the levels of U-Prot in the advanced IgAN cases (20,21), and the decreases in the levels of U-Prot caused by ARBs were greater than those caused by ACEIs in these cases (19). In addition, we could not deny that these differences between the groups accounted for the lack of significant decreases in the levels of U-Prot in the DILAZEP group, although the ability of RASIs to decrease the levels of U-Prot is widely recognized.…”
Section: Discussioncontrasting
confidence: 69%
“…Several previous reports from various countries have facilitated a full understanding of the renoprotective effects of RASIs (11)(12)(13). Results from our laboratory have also demonstrated the beneficial effects of these medications, especially in patients with advanced IgAN with an impaired renal function (19)(20)(21), a condition for which fish oil therapies, including the omega-3 polyunsaturated fatty acids (PUFA) eicosapentaenoic acid and docosahexaenoic acid (DHA), are also beneficial, as reported by several groups (22)(23)(24)(25). In an elegant series of studies, Donadio and colleagues reported the short-and long-term beneficial effects of fish oil on IgAN using a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 62%
“…16 It was reported that ACEI/ARB was effective as same as steroids for longterm renal survival of advanced IgAN. 20 However, the beneficial effects of ACEI/ARB on advanced IgAN were independent of the reduction of proteinuria and blood pressure. 19 The histological findings of the renal biopsy specimens showed approximately 65% of all IgAN patients weeks, TGF-b1, FN, a-SMA and FGF-1 expressions in the model group were significantly up-regulated as compared with the control group (p50.05).…”
Section: Discussionmentioning
confidence: 99%
“…20 Steroids or immunosuppressive agents can repair active lesions, but does not affect chronic lesions and the remaining glomeruli with glomerular hypertension and hyperfiltration. Although ARB therapy does not affect active lesions, it can reduce glomerular hypertension and hyperfiltration of the remaining glomeruli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation